Implementation of RPA in Processing Data to Increase Efficiency in Danone’s Supply Chain Department (Journal of Business and Management, 2022)
Technology development has been an inevitable phenomenon. What human can do as the user of technology is to utilize it for good reasons. For instance, implementing technology to help human deal with their limitations at work. Danone, a multinational food producing company, chose to implement a technology that helps them in processing data. The technology is RPA or Robotic Process Automation, it automates many kinds of process that happen in the department. This study compares the differences between using RPA or just process the data manually. Adding to that, this study also looks for changes that has been made in order to increase their work efficiency beside the implementation of RPA. It was found that implementing RPA to automate repetitive tasks that might drain human energy is working well. The interview respondents mentioned that RPA works exceptionally for time-saving aspect while still offering the same quality of output since they have the same accuracy with the one previously. Although, RPA as an enhancement for their overall performance was added, RPA sometimes encounter errors in its’ running process and found that it was because of the human intervention that happen. This study identifies all the changes and readjustments that happen after using RPA and looking for its’ impact. Also, the study helps the company find any necessary refinement that can increase overall performance of the department. This study also designed 3 scenarios that can be used to prevent further human intervention. Some of them are drawn in flowchart to be added in the RPA order program as a recommendation for the refinement.Keywords: Robotic Process Automation (RPA), Efficiency, Data Processing, Readjustment.